2011
DOI: 10.1007/s10792-011-9455-7
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal voriconazole for the treatment of Aspergillus chorioretinitis

Abstract: The aim of this article is to report a case of Aspergillus chorioretinitis successfully treated with intravitreal voriconazole based on an interventional case report. An immunodeficient patient, 34 years old, receiving systemic antifungal treatment for 1 month for invasive aspergillosis with necrotizing pneumonia and brain metastasis, who presented with blurred vision in his left eye. Visual acuity (VA) was 20/20 in his right eye, and 8/20 in his left eye. Ophthalmological examination showed a paramacular nodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…36 Vila Arteaga J et al, in their case study had a significant and rapid improvement in patient treated with single dose of injection intravitreal voriconazole (100 μg/0.1 ml) for aspergillus chorioretinitis, obviating the need for vitrectomy. 37 Jang GJ et.al, successfully treated aspergillus chorioretinitis with systemic voriconazole. 38 …”
Section: Major Reviewmentioning
confidence: 99%
“…36 Vila Arteaga J et al, in their case study had a significant and rapid improvement in patient treated with single dose of injection intravitreal voriconazole (100 μg/0.1 ml) for aspergillus chorioretinitis, obviating the need for vitrectomy. 37 Jang GJ et.al, successfully treated aspergillus chorioretinitis with systemic voriconazole. 38 …”
Section: Major Reviewmentioning
confidence: 99%
“…Voriconazole is a second generation triazole which acts on the enzymes of the fungal cytochrome P450, preventing the synthesis of ergosterol in the cytoplasmic membrane, thus inhibiting fungal growth [ 1 , 14 , 16 , 17 ]. It has shown therapeutic efficacy against fungal keratitis and endophthalmitis after intrastromal, intracameral, intravitreal, intravenous, oral, and topical administration [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. It has strong biological activity against Candida , Aspergillus , Fusarium, and other filamentous fungal species [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have concluded that intravitreal VCZ could be a treatment strategy for fungal endophthalmitis. [8][9][10][11][12] Amphotericin B (Amp-B) is the treatment of choice for fungal endophthalmitis. Amphotericin B increases fungal membrane permeability and cell death by binding ergosterol.…”
mentioning
confidence: 99%